Abiotic Stress in Plants 2021
DOI: 10.5772/intechopen.93824
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stress Responses in Plants: Current Knowledge and Future Prospects

Abstract: Exposure to abiotic stresses has become a major threatening factor that hurdles the sustainable growth in agriculture for fulfilling the growing food demand worldwide. A significant decrease in the production of major food crops including wheat, rice, and maize is predicted in the near future due to the combined effect of abiotic stresses and climate change that will hamper global food security. Thus, desperate efforts are necessary to develop abiotic stress-resilient crops with improved agronomic traits. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 111 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…This fact of accumulation of proteins/amino acids is confirmed in banana by El-Mahdy et al (2018) who reported that the concentration of phenols and proline increased in cultivars 'Grand Naine' and 'Williams' under cold stress. Abiotic stresses induce shift in photosynthetic activities in plant (Marothia et al, 2020).…”
Section: Physiological Effectmentioning
confidence: 99%
“…This fact of accumulation of proteins/amino acids is confirmed in banana by El-Mahdy et al (2018) who reported that the concentration of phenols and proline increased in cultivars 'Grand Naine' and 'Williams' under cold stress. Abiotic stresses induce shift in photosynthetic activities in plant (Marothia et al, 2020).…”
Section: Physiological Effectmentioning
confidence: 99%
“…Plants are sessile organisms and abiotic stressors, including drought, salt and severe temperatures, must be endured by them [ 3 ]. Stress responses are complex, integrated circuits rather than simple, linear routes, incorporating several pathways, particularly cellular compartments, tissues and interactions with extra cofactors and/or signaling molecules to coordinate a specific response to a given stimulus [ 4 ]. The tissue or organ that is under stress will determine how the plant reacts.…”
Section: Introductionmentioning
confidence: 99%
“…Plants affected by these abiotic stresses have evolved several morphological, physiological, and molecular responses (Körner, 2003). Regarding physiological defensive strategies, a combination of elements allows plants to avoid and/or tolerate damages produced by these abiotic stresses (Banerjee & Roychoudhury, 2019; Germino & Smith, 2000; Marothia et al, 2020). One of the processes highly affected is photosynthesis (Gururani et al, 2015), a key biological process that determines growth and development, and ultimately the vigor of plants at every development stage.…”
Section: Introductionmentioning
confidence: 99%